Heat Transfer During Forest Biomass Particles Drying in an Agitated Fluidised Bed - Reyes-Salinas, A (Academic Press, 2016)
The phenomenon of convective heat transfer between gas and biomass particles during the drying process of fluidised bed material was analysed in order to obtain the heat transfer coefficients between the gas and the particle surface. In order to promote high homogeneity of the particles suspension, the bed was mechanically stirred, to obtain a uniform temperature inside the bed. The results showed a correlation between, the Nusselt and Reynolds numbers, which predicts the surface heat transfer coefficient with a deviation of ±15%, in relation to the experimental data. © 2016 IAgrE